IT’S PINK! redesigning Laura Street into a smart model for gender-responsive planned unit development towards social reproduction - De Guzman, Julienne Marie R.; Lacson, David Xander T. (Quezon City College of Architecture, University of the Philippines Diliman, 2024)
Women are perceived as having a small participation in the city due to the gender roles that reinforce architecture (Rendell, 2000). The separation between the public and private spheres is evidence of women’s oppression that surpasses the spatial and social dimensions. Starting from the space that closely boxes women’s role in society— the house, followed by the dimensions of the complexities that respond to women’s multiple responsibilities. The study seeks to reinterpret and restructure the built environment with women in mind. Patterns of user behavior, perception, and activities were analyzed through a series of in-depth interviews and codesign sessions with the residents of the Laura Compound, along with the phenomenological standpoint of the author. Overarching the developed themes from the case study and literature review spaces responsive to women were identified along with the necessary facilities in the enclave. With the partnership of the community in Laura, Matandang Balara, and the Quezon City LGU, the project aims to propose a mixed-use residential smart enclave situated in Quezon City that addresses (1) contextualized activities, needs, and issues of low-income women while considering (2) SMART City components and (3) bridging it into a gender-responsive approach in designing. The potential use of the Laura compound as a mixed-use residential smart enclave will not only augment the invisibilization of low-income women in the city, but also address the long-sought misogynistic implications of the urban environment.
Include appendices
Thesis (Bachelor of Science in Architecture) -- University of the Philippines Diliman
Keywords: Mixed-use developments -- Matandang Balara; Housing -- Matandang Balara; Women -- Social aspects -- Matandang Balara; Housing -- Social aspects -- Matandang Balara